Pengaruh Penambahan Tepung Bengkuang Terhadap Kadar Kalsium Susu Kedelai - Ambarwani, Ambarwani; Mahanany, Destyna; Wardhani, Dipicha Triesnaputri Kusuma; Kurnia, Pramudya (Jurnal Kesehatan, 2013)
Calcium deficiency in adolescence and early adulthood may increase risk of osteoporosis. Theprevalence of osteoporosis of Indonesia population in 2005 was 10.3%, whereas for young people(below 25 years) was 37.1%, and for young adult women was 39.5%. One way to prevent osteopeniaand osteoporosis is to consume cow?s milk. The problem is the high price of cow?s milk, so the otheralternative is soy milk. The calcium of soy milk, however, is lower than cow?s milk. Yam is tuber that isrich in calcium and phosphorus. The completely random design was used with 4 treatments of yam flouradded to soy milk, were 0% (control), 2.5%, 5%, and 7.5%. The calcium content was determined usingAAS. Data were analyzed using anova, followed by Duncan. The result displayed that optimum ofcalcium content was indicated by addition of yam flour 5 %. The conclusion is there is the effect of yamflour addition on calcium level of soy milk.